Psychosocial effects assocPsychosocial effects associated with highly pathogenic avian influenza (H5N1) in Nigeriaiated with highly pathogenic avian influenza (H5N1) in Nigeria - Chiara Rafanelli; Sara Gostoli; Yuri Milaneschi; Victoria Pam; Godman E. Jonah; Oludayo F. Fasina (Veterinaria Italiana, 2010)
Highly pathogenic avian influenza H5N1 (HPAI H5N1) infected poultry in Nigeria in 2006. The outbreaks caused significant economic losses and had serious zoonotic repercussions. The outbreaks have also had psychosocial effects on Nigerian farmers. To date, empirical data on the effect of outbreaks on humans are scarce. In this study, field data on HPAI H5N1 in Nigeria were analysed. Although only one human case leading to death was reported in Nigeria, the fact that HPAI H5N1 caused a human death created a disruption in social order and in the well-being of farmers (stress, altered livelihood and trauma) and affected the rural economy. The implication of the above on health communication, the importance of successful control measures in poultry and policy implementation are stressed. Further studies are encouraged.